Parathyroidectomy Improves Restless Leg Syndrome in Patients on Hemodialysis - Santos, Roberto Sávio Silva (PLoS One, 2016)
BACKGROUND: Restless leg syndrome (RLS) is a sleep disorder with high prevalence among patients on hemodialysis. It has been postulated that high phosphate and high parathyroid hormone may be implicated in its pathogenesis. Standard international criteria and face-to-face interview are not always applied. METHODS: this was an interventional prospective study in which 19 patients (6 men, aged 48±11 years) with severe hyperparathyroidism were evaluated. RLS diagnosis and rating scale were accessed based on the International RLS Study Group pre- and post-parathyroidectomy. Patients also underwent standard polysomnography. RESULTS: At baseline, RLS was present in 10 patients (52.6%), and pain was the most reported symptom associated with the diagnosis. Patients with RLS had higher serum phosphate (p = 0.008) that remained independently associated with RLS in a logistic regression model, adjusted for hemoglobin, age and gender (HR = 7.28;CI = 1.14–46.3, p = 0.035). After parathyroidectomy, there was a reduction of serum parathyroid hormone, phosphate, calcium and alkaline phosphatase, and an increase of 25(OH)-vitamin D, and Fetuin-A. Parathyroidectomy alleviated RLS (from 52% to 21%; p = 0.04), which was accompanied by a decrease in severity scale, in association with relief of pain and pruritus. Polysomnography in these patients showed an improvement of sleep parameters as measured by sleep efficiency, sleep latency and percentage of REM sleep. CONCLUSION: RLS is associated with high levels of phosphate in patients with severe secondary hyperparathyroidism on hemodialysis. Pain is most reported complain in these patients. Parathyroidectomy provided an opportunity to relief RLS. Whether the reduction of serum phosphorus or parathyroid hormone contributed to this improvement merits further investigation.